2012
DOI: 10.1111/j.1464-410x.2012.11240.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of non‐voiding activity by the muscarinergic antagonist tolterodine and the β3‐adrenoceptor agonist mirabegron in conscious rats with partial outflow obstruction

Abstract: Non-voiding activity is sensitive to muscarinergic antagonists and β(3)-adrenoceptor agonists, but there are clear differences between the two drugs. A model is proposed to account for these observations where both agents act on a 'pacemaker-like' mechanism with cholinergic excitatory and adrenergic inhibitory inputs. Such concepts may provide insights into the nature of overactive bladder and the site of action of key therapeutic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
51
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 38 publications
7
51
0
Order By: Relevance
“…In addition, organ bath data on mirabegron showed that the drug relaxed normal urinary bladder strips with about threefold lower potency as isoprenaline (Takasu et al 2007). On the other hand, the activity of mirabegron to modulate the voiding cycle (Sadananda et al 2013) and decrease NVA in rat (Gillespie et al 2012; current study) was found at similar dose equivalents. Therefore, the latter situation is likely to represent a β 3 -AR mechanism.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…In addition, organ bath data on mirabegron showed that the drug relaxed normal urinary bladder strips with about threefold lower potency as isoprenaline (Takasu et al 2007). On the other hand, the activity of mirabegron to modulate the voiding cycle (Sadananda et al 2013) and decrease NVA in rat (Gillespie et al 2012; current study) was found at similar dose equivalents. Therefore, the latter situation is likely to represent a β 3 -AR mechanism.…”
supporting
confidence: 53%
“…PGE 2 clearly increased NVA, not only during bladder filling, but also at isovolumetric conditions, and the latter condition allowed to quantify the dose-dependent effect of mirabegron to inhibit the phenomenon of NVA. In an earlier paper, Gillespie et al (2012) showed dose-dependent inhibition of NVA integral by mirabegron in pBOO rats.…”
mentioning
confidence: 97%
“…In another study in rats with bladder outlet obstruction, non-voiding activity consisted of small and large transients and i.v. administration of both mirabegron and tolterodine reduced the cumulative activity of the large non-voiding contractions but had little effect on the small transients (Gillespie et al 2012). In that study, mirabegron primarily reduced the frequency of such contractions, whereas tolterodine mainly reduced their amplitude.…”
Section: In Vivo Animal Studiesmentioning
confidence: 71%
“…Interstitial cells were found to be excitable and able to transmit their electrical activity to the detrusor cells via gap junctions to generate propagating waves of contraction in the bladder wall Gray et al, 2013;Hashitani et al, 2004). It has been speculated that such an agonist stimulated, phasic and coordinated phenomenon of contractions may be related to the NVA seen during cystometric studies in conscious animals (Gillespie et al, 2012) and might be involved in the generation of bladder sensations (Eastham and Gillespie, 2013;Gillespie, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Alternative ideas have been put forward regarding the mode of action of mirabegron, for example, afferent recording from mechanosensitive afferents have been shown to be decreased in the presence of mirabegron, an effect possibly linked to inhibition of MC activity (Aizawa et al, 2012). In an obstructed rat model, it was shown that mirabegron reduced NVA, having little effect on detrusor contractility during voids, suggesting that this motor-sensory system might be a potential therapeutic target for β 3 -selective adrenoceptor agonists (Gillespie et al, 2012). In addition, other targets have been suggested that include the urothelium (Kullmann et al, 2011;Masunaga et al, 2010) or pelvic ganglia (Eastham et al, 2015).…”
Section: Introductionmentioning
confidence: 97%